Perception of Rural and Urban Mothers about Consumption of Targeted Fortified Products in Jaipur, Rajasthan - India: A Cross-Sectional Study - Anup Nagaraj; Asif Yousuf; Shravani Ganta (Health Promotion Perspectives, 2013)
Background: Food fortification is the addition of one or more essential nutrients to a food whether or not it is normally contained in the food, for the purpose of preventing or correcting a demonstrated deficiency of one or more nutrients in the population or specific population groups. The present cross-sectional study was conducted to obtain comprehensive in¬formation towards consumption of Targeted Fortified Products (TFP) among rural and urban mothers of children < 3 years in Jaipur, India.Methods: In this cross-sectional study conducted in 2012, three hundred rural and urban mothers were selected from Primary Health Centre, Ach¬rol Village and Uniara Hospital in Jaipur, Rajasthan. The data were col¬lected using a self-administered questionnaire. The current nutritional sta¬tus of children was determined by anthropometric measurements. Results: A total of 53.33% rural and 65.33% urban mothers had know¬ledge (P=0.046), amongst which 52.67% rural and 66.00% urban mothers (P= 0.026) consumed TFP directed towards mothers. In addition, 56% rural and 94.67% urban mothers had knowledge (P=0.000) about TFP directed towards children, amongst which 19.33% rural and 50.67% urban mothers (P=0.000) fed their children with TFP.Conclusion: There was significantly less awareness regarding consump¬tion of TFP directed towards both pregnant women and children among rural when compared to urban population. Attitudes seemed to be go¬verned by the traditional beliefs and family influences of region rather than the knowledge obtained. There is a need of intensive coordinated efforts to create awareness among mothers to enhance the maternal and child diets through TFP.